Seven elements that changed the world : an adventure of ingenuity and discovery - Browne, John (New York, NY : Pegasus Books, 2004)
Combining true stories from the worlds of history, science, and politics, describes how the use of seven elements--iron, carbon, gold, silver, uranium, titanium, and silicon--has changed the world for both the better and worse.
The essence of everything -- Iron -- Carbon -- Gold -- Silver -- Uranium -- Titanium -- Silicon -- Power, progress and destruction.
Keywords: Chemical elements -- Popular works; Technology -- Social aspects; Chemical elements